PENGGUNAAN INTERNET DAN EMPATI SISWA DI SMK LABOR BINAAN FKIP UNRI PEKANBARU - Oktarumaila Oktarumaila; Rosmawati Rosmawati; Tri Umari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The progress in ancient times happened impact to various aspect of human life. Use the internet seemed to be need of society. The internet has been used by many people, one of them is student. In addition, the progress in the world of education can not be separated from technological progress that is always hand in hand. Therefore the writer interest to do a research about. The purpose of this research are to know the general idea about user of internet in SMK Labor Binaan FKIP UNRI Pekanbaru and the general idea about emphaty level of students SMK Labor Binaan FKIP UNRI Pekanbaru. This research uses descriptive methode with the technique of collecting the is questionnaire. To analyze the data use percentage formula. The subject in this research is students of class X and XI. The total participant are 110 student. The result of the research, the write found that user of internet from students SMK Labor Binaan FKIP UNRI Pekanbaru category that is equal. While the level of empathy students SMK Labor Binaan FKIP UNRI Pekanbaru his in the high category that is equal.Keyword : Empathy, Internet, Student.